EMPOWERING PETERNAK SAPI MELALUI PENINGKATAN LITERASI DAN AKSES PEMBIAYAAN SYARIAH DI SEKITAR KECAMATAN LUBUK KILANGAN - Wahyudi, Rahmat; Rici, Suchi Avita (Jurnal Abdi Insani, 2025)
Cattle farmers in Lubuk Kilangan District face the challenges of low financial literacy and limited access to financing that complies with Sharia principles. This condition hampers capital management and livestock business development, as many farmers do not maintain proper financial records, making it difficult to obtain formal financing support. Furthermore, understanding of Sharia financing products remains limited, causing them to rely on high-risk informal financing. This program aims to improve Sharia financial literacy and expand access to Sharia financing for partner cattle farmers. The implementation method includes counseling, training, simulation, mentoring, and evaluation using a participatory approach, with pre-test and post-test instruments to measure improvements in participants’ knowledge and skills. The results showed significant increases in three main indicators: financial literacy (from 55% to 85%), understanding of Sharia financing (from 48% to 82%), and awareness of informal financing risks (from 52% to 84%). Additionally, 90% of participants committed to applying daily financial recording, 85% planned to separate personal and business finances, and 80% were interested in applying for Sharia financing within the next six months. The program also successfully established an initial network between farmers and Sharia financial institutions, opening opportunities for sustainability, and is feasible to be replicated in other regions with local adjustments. Keywords: Financial literacy, Sharia financing, Farmer empowerment, Community service, Cattle farming business.